Prognostic clinical factors associated with remission and relapse in bullous pemphigoid. (16th July 2016) - Lee, J.H.; Kim, T.H.; Park, S.H.; Han, K.; Kim, S.‐C.
Abstract: Background: Prognostic factors for remission and relapse of bullous pemphigoid (BP) remain uncertain. Objective: To evaluate clinical factors associated with remission and relapse in Korean patients with BP. Methods: A retrospective analysis was conducted of 174 patients diagnosed with BP between 1993 and 2014 at Gangnam Severance Hospital in Seoul, Korea. Results: Of the 174 identified patients, 131 (75.29%) achieved remission after a mean treatment duration of 393.69 days. Prognostic factors for remission were older age (≥70 years) and the absence of an admission history. Of 131 patients who achieved remission, 40 patients (30.53%) experienced relapse after a mean duration of 335.65 days. However, no statistically significant factors were predictive of relapse by multivariate analysis. Conclusions: This study suggests BP patients who are older and have no admission history tend to achieve remission.